1996
DOI: 10.1177/096032719601500507
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced alterations in blood- brain barrier permeability and its possible correlation with decreased microvessel antioxidant potential in rat

Abstract: 1 Male albino rats of 21 days age were exposed to 10 p.p.m. cadmium (CdCl2 salt) in drinking water, ad libitum, for 90 days. It increased the brain cadmium levels by 76% ( P < 0.05) and 165% ( P < 0.001) respec tively at 30 and 90 days of exposure compared to controls. 2 Cadmium increased blood - brain barrier permeability of fluoroscein dye (24%, P < 0.02) and the levels ofbrain microvessel malondialdehyde (31%, P<0.01) at 90 days of exposure. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(113 citation statements)
references
References 23 publications
3
106
0
4
Order By: Relevance
“…However, Kostić et al (11) indicated that the chronic exposure of Cd decreases the level of iron in the blood and causes the decrease of the RBC count, hemoglobin concentration and hematocrit value. The decrease of hematocrit value in hemolyzed plasma of rats exposed to Cd indicates the increased destruction of RBCs (43,44). It was found in this work that the RBC counts decreased in Cd treated rats.…”
Section: Discussionsupporting
confidence: 59%
“…However, Kostić et al (11) indicated that the chronic exposure of Cd decreases the level of iron in the blood and causes the decrease of the RBC count, hemoglobin concentration and hematocrit value. The decrease of hematocrit value in hemolyzed plasma of rats exposed to Cd indicates the increased destruction of RBCs (43,44). It was found in this work that the RBC counts decreased in Cd treated rats.…”
Section: Discussionsupporting
confidence: 59%
“…Aktywność enzymów w surowicy krwi zależy w dużym stopniu od stanu fizjologicznego zwierząt, w tym stanów chorobowych, diety (żywienia), a także czynników środowiskowych, w tym obecności substancji toksycznych (18,41,42,45). Uzyskane wyniki wskazują na pewne różnice między rejonami badań (tab.…”
Section: Wyniki I Omówienieunclassified
“…Przy intoksykacji Pb aktywność tych enzymów (m.in. SOD, GSH-Px, MDA) istotnie się obniża (42). Z kolei badania Gong i Xiao (19) potwierdzają nasilenie stresu oksydacyjnego u krów na początku laktacji, co wynika ze wzrostu poziomu MDA, przy obniżeniu TAS.…”
Section: Wyniki I Omówienieunclassified
“…Cd also enhances the production of free radicals in the brain of adult rats and interferes with the antioxidant defense system that in turn leads to a Cd-induced alteration of the structural integrity of lipids (Shukla et al, 1996). In adult rats exposed to Cd, there was an increase of LP in the corpus striatum and cerebral cortex (Pal et al, 1993).…”
Section: Discussion:-mentioning
confidence: 99%